2021
DOI: 10.1016/j.econlet.2021.109812
|View full text |Cite
|
Sign up to set email alerts
|

Learning during the COVID-19 pandemic: It is not who you teach, but how you teach

Abstract: We use standardized end-of-course knowledge assessments to examine student learning during the disruptions induced by the COVID-19 pandemic. Examining seven economics courses taught at four US R1 institutions, we find that students performed substantially worse, on average, in Spring 2020 when compared to Spring or Fall 2019. We find no evidence that the effect was driven by specific demographic groups. However, our results suggest that teaching methods that encourage active engagement, such as the use of smal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
43
0
6

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 97 publications
(75 citation statements)
references
References 11 publications
3
43
0
6
Order By: Relevance
“…There is a move towards a more holistic paradigm, where learning is more integrative and organized around problems, instead of specific discipline content. This learning approach is aligned with the most recent research, which has found that such pedagogies are more effective at fostering better learning outcomes (Nathan & Sawyer, 2014).…”
Section: Constructivism/learner-centered Educationsupporting
confidence: 66%
“…There is a move towards a more holistic paradigm, where learning is more integrative and organized around problems, instead of specific discipline content. This learning approach is aligned with the most recent research, which has found that such pedagogies are more effective at fostering better learning outcomes (Nathan & Sawyer, 2014).…”
Section: Constructivism/learner-centered Educationsupporting
confidence: 66%
“…The question is whether the disproportions in problems experienced by students with and without reading difficulties will be observable even after the COVID-19 pandemic, when the on-site classes will be returned (even to some extent) or when the COVID-19 threat will be lowered (e.g., after vaccinating the population of students). It is also interesting whether now disadvantaged groups like students with dyslexia (or more broadly saying-with specific learning difficulties) would be further disadvantaged due the remote learning as the pandemic continue or will they accumulate some experience in remote learning which may facilitate the learning process and increase learning outcome as suggested by Orlov and colleagues (Orlov et al, 2021). To find this out, in the future, it would be advisable to continue similar research, as well as include standardized measurements of distress related to the COVID-19 pandemic.…”
Section: Future Research Directionsmentioning
confidence: 99%
“…Developing these issues, in our research we proposed an approach to the assessment of knowledge improvement on the example of a small group of students. The results of the observations indicate that conducting classes in small groups of students encourages them to be actively involved and at the same time plays an important role in mitigating the effects of Covid-19 on student learning [82]. At the same time, the question is not only of who you teach but how you teach [82] taking into account elements of educational technology and high and low achieving students [83].…”
Section: Discussionmentioning
confidence: 96%